Differential effects of sound intervention and rest on cardiovascular parameters in cancer patients: a randomized cross-over trial - Hohneck, Anna; Hofheinz, Christina; Merx, Kirsten; Weingärtner, Simone; Mavratzas, Athanasios; Schumacher, Gerhard; Linhuber, Christoph; Hofmann, Wolf-Karsten; Burkholder, Iris; Hofheinz, Ralf-Dieter (Integrative cancer therapies, 2021)
Background:Music therapy or sound interventions were shown to confer beneficial effects in patients with cancer for instance in terms of pain or fear relief and improvement of other patient reported outcomes. Cardiovascular parameters, especially heart rate variability (HRV) were found to have prognostic implications in cancer patients. In this trial we aimed to investigate the effects of a sound intervention on cardiovascular parameters compared to rest in patients with cancer.Methods and results:Using a randomized cross-over design, 52 patients (male 13, female 39) with cancer were recruited to receive both a 15-minute sound intervention and a 15-minute rest intervention within 4?weeks with at least a one-week blanking period. Cardiovascular parameters (among others HRV, aortic pulse wave velocity [PWV], augmentation index [Aix], aortic blood pressure [BP], heart rate [HR]) were assessed immediately before (pre) and after (post) the intervention had taken place. HRV (Root mean square of successive RR interval differences [RMSSD, ms]) significantly increased, during sound intervention (median RMSSD pre 24 [range 5-112] vs post 22 [range 9-141], P?=?.03). Likewise, median PWV, as a direct marker of arterial stiffness, was significantly reduced by sound intervention ([m/s] pre 8.5 [range 5.6-19.6] vs post 8.3 [range 5.6-15.6], P?=?.04). For both parameters no statistically significant change during rest was observed. HR was lowered by both, rest (P?
Gesehen am 28.07.2021